PENGELOLAAN ALOKASI DANA DESA PADA DESA NGATABARU KECAMATAN SIGI BIROMARU KABUPATEN SIGI - Sumiati, Sumiati (Katalogis, 2015)
This research aims at determining the village fund allocation management in the Village Nagatabaru of Sub district Sigi Biromaru, District Sigi. The researcher uses a qualitative method with number of five informants. The researcher uses the method of observation (observation), interviews, and documentation in collecting the data. the village fund allocation management in the Village Nagatabaru of Sub district Sigi Biromaru, District Sigi uses the theory of George R. Terry consisting of management functions: planning, organizing, actuating, and controlling. The results shows that the village fund allocation management in the Village Nagatabaru of Sub district Sigi Biromaru, District Sigi is not going well in terms of planning, organizing, implementing, and monitoring. Careless planning factor, in terms of organizing, there is not any main job and function description, whilst in terms of actuating, accountability of village fund allocation is not punctual, as well as embedded control is not carried out periodically.